The reasons of difficulties in health education according to the nurses working at school - Leńczuk-Gruba, Anna; Kobos, Ewa; Wrońska, Irena (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Introduction. Health education is an important space at nursing care at school. In performed this procedure nurse can meet many difficulties. The nurse should research and find out any factors or circumstances connected with problems of health education. This can help her in realization a procedure of health education. Aim. The aim of the research was to assess the reasons of problems in health education performed by a nurses in a school environment. Material and methods. The authorship questionnaire have been distributed to 102 nurses working at schools in Warsaw. Results and conclusions. The nurses pointed out the following difficulties: not enough time for health education in general planning at school, limited time of nursing visits, lack of cooperation between parents and school nurse.